2016
DOI: 10.1088/0957-4484/27/38/385503
|View full text |Cite
|
Sign up to set email alerts
|

A new method to integrate ZnO nano-tetrapods on MEMS micro-hotplates for large scale gas sensor production

Abstract: A new method, which is easily scalable to large scale production, has been developed to obtain gas sensor devices based on zinc oxide (ZnO) nanostructures with a 'tetrapod' shape. The method can be easily extended to other kinds of nanostructures and is based on the deposition of ZnO nanostructures through polymeric masks by centrifugation, directly onto properly designed MEMS micro-hotplates. The micromachined devices, after the mask is peeled off, are ready for electrical bonding and sensing test. Sensor res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In comparison with the various nanostructured SnO 2 prepared by other methods in Table 1, the crosslinked SnO 2 /NiO network exhibited comparable sensitivity [19,23,47,[49][50][51][52]. We also investigated the ethanol sensitivity of other MEMS compatible sensing materials in Table 1, such as DPN deposited Au/SnO 2 nanocomposites, ZnO nanowires grown on a MEMS microplate, and ZnO tetrapods deposited on a microheater [37,38,51]. Apart from the comparable or better sensitivity, there are several other advantages for the cross-linked SnO 2 /NiO networks including high yield, low device-to-device deviation, cheap and simple processing.…”
Section: Gas-sensing Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the various nanostructured SnO 2 prepared by other methods in Table 1, the crosslinked SnO 2 /NiO network exhibited comparable sensitivity [19,23,47,[49][50][51][52]. We also investigated the ethanol sensitivity of other MEMS compatible sensing materials in Table 1, such as DPN deposited Au/SnO 2 nanocomposites, ZnO nanowires grown on a MEMS microplate, and ZnO tetrapods deposited on a microheater [37,38,51]. Apart from the comparable or better sensitivity, there are several other advantages for the cross-linked SnO 2 /NiO networks including high yield, low device-to-device deviation, cheap and simple processing.…”
Section: Gas-sensing Performancementioning
confidence: 99%
“…Second, some researchers have tried to integrate high-performance MOS nanomaterials onto microheaters, but it is difficult to control and cast the slurry-based MOS nanomaterials onto the suspending heating area of microheaters. Several groups have reported the fabrication of nanomaterialbased MEMS sensors via ink-jet printing, polymeric mask centrifugation, and dip pen nanolithography (DPN) methods [12,[36][37][38][39]. However, the low yield and large device-to-device deviation hampers the sensor fabrication in a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…More generally downscaling is considered an essential evolution of devices in the field of integrated circuit (IC) and micro electro mechanical system (MEMS). The typical advantages envisaged are the compactness, low energy consumption, and large scale production . The typical fees to pay are related to device heating issues, standard photolithography resolution limits, process compatibility, and process optimization with respect to all the possible critical steps.…”
Section: Introductionmentioning
confidence: 99%
“…Low power consumption is an important parameter in evaluating the properties of MEMS gas sensors. It has been widely reported that researchers can improve the performance of gas sensors by constantly optimizing the micro-hotplatform (MHP) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) structure and the morphology of sensing materials. (15)(16)(17)(18)(19) For example, in earlier research on MEMS gas sensors, Lee et al (4) described the great advantage of low power consumption compared with traditional gas sensors.…”
Section: Introductionmentioning
confidence: 99%